A Convenient and Stable Heterogeneous Nickel Catalyst for Hydrodehalogenation of Aryl Halides Using Molecular Hydrogen. Issue 5 (11th February 2022) - Leonard, David K.; Ryabchuk, Pavel; Anwar, Muhammad; Dastgir, Sarim; Junge, Kathrin; Beller, Matthias
Abstract: Invited for this month′s cover is the group of Matthias Beller at the Leibniz Institute for Catalysis in Rostock in collaboration with Muhammad Anwar and Sarim Dastgir at the Qatar Environment and Energy Research Institute in Doha. The image illustrates a hydrodehalogenation of polybrominated diphenyl ether (PBDE) using a heterogeneous nickel catalyst supported on titanium oxide and dihydrogen. The Research Article itself is available at 10.1002/cssc.202102315 . Abstract : "…there was a need to find a safe and highly active non‐noble catalyst for hydrodehalogenation of polyhalogenated substrates." This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202102315 . View the Front Cover here: 10.1002/cssc.202200247 .